Проходные емкости в кабелях с экранированными витыми парами - Федяй, Анна Сергеевна (НТУ "ХПИ", 2017)
Особенностью конструкции контрольных кабелей с экранированными витыми парами является гибкий проволочный экран, наложенный на симметричную пару изолированных жил поверх скрепляющей пленки. В зазоры, образованные проволоками экрана может проникать слабое электрическое поле. Измеряя проходные емкости между парами можно получить информацию о состоянии межэкранного пространства контрольного кабеля. Величины проходных емкостей настолько малы, что корректное их измерение возможно осуществить только совокупным методом.

The design feature of control cables with shielded twisted pairs is a flexible wire screen imposed on a symmetric pair of insulated wire on top of the fastening tapes. Between the wires of the screen there are gaps through which can penetrate a weak electric field. Measuring the so-called feedthrough capacitance between the pairs you can get information about the state of the space between the screens of control cables. For the assessment of the values feedthrough capacitance made mathematical modeling of the two shielded twisted pairs electric fields, which takes into account the surface density of the screen. The field strength between the pairs in the so-called scope of weak field reaches 10 kV/m, the feed-through capacitance does not exceed a few hundredths picofarads per meter of cable length. So small values is possible to correctly measure by the aggregate method.
Feedthrough capacitance in cables with shielded twisted pairs
Keywords: проволочный экран; оплетка; межэкранное пространство; коэффициент поверхностной плотности; wire screen; space between the screens